2008
DOI: 10.1186/1471-213x-8-85
|View full text |Cite
|
Sign up to set email alerts
|

Onset of meiosis in the chicken embryo; evidence of a role for retinoic acid

Abstract: Background: Meiosis in higher vertebrates shows a dramatic sexual dimorphism: germ cells enter meiosis and arrest at prophase I during embryogenesis in females, whereas in males they enter mitotic arrest during embryogenesis and enter meiosis only after birth. Here we report the molecular analysis of meiosis onset in the chicken model and provide evidence for conserved regulation by retinoic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(184 citation statements)
references
References 36 publications
7
174
2
1
Order By: Relevance
“…cSYCP1 and cSYCP2 were initially expressed on E6.0 in both testis and ovary, whereas cSYCP3 was initially expressed on E6.0 in females and on E8.0 in males. The onset of meiosis in chickens occurs first in female gonads on E15.5 (Smith et al 2008). The duration-dependent expression of cSYCP family members in the present study calls into question the idea that cSYCP family members are specific to meiotic prophase I or are initially expressed only after pre-meiotic development of germ cells.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…cSYCP1 and cSYCP2 were initially expressed on E6.0 in both testis and ovary, whereas cSYCP3 was initially expressed on E6.0 in females and on E8.0 in males. The onset of meiosis in chickens occurs first in female gonads on E15.5 (Smith et al 2008). The duration-dependent expression of cSYCP family members in the present study calls into question the idea that cSYCP family members are specific to meiotic prophase I or are initially expressed only after pre-meiotic development of germ cells.…”
Section: Discussionmentioning
confidence: 38%
“…The same RNA samples were hybridised with probes made from the endogenous housekeeping gene, chicken glyceraldehyde-3-phosphate dehydrogenase (cGAPDH) for normalisation. numerous in the female gonad (Hughes 1963, Smith et al 2008. In male chickens, PGCs undergo mitotic arrest: they stop dividing and remain as pro-spermatogonia at the G1 stage of the cell cycle until hatching (Kirby & Froman 2000, Smith et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…In the female embryo, miR181a* expression was down-regulated gradually as female embryonic gonads developed; however, the NR6A1 transcript was increased dramatically, particularly around day 13.5. Smith et al (39) reported that germ cells in the chicken female gonad initiate meiosis at around E12.5, at which time STRA8 is up-regulated in the female left gonad. In contrast to the female embryo, miR181a* was highly expressed in male embryonic gonads; however, NR6A1 expression was suppressed after E13.5 (39).…”
Section: Specific Analysis Of the Target Gene Transcript For The Regumentioning
confidence: 99%
“…Smith et al (39) reported that germ cells in the chicken female gonad initiate meiosis at around E12.5, at which time STRA8 is up-regulated in the female left gonad. In contrast to the female embryo, miR181a* was highly expressed in male embryonic gonads; however, NR6A1 expression was suppressed after E13.5 (39). Thus, we propose that miR-181a* and NR6A1 could be closely related to the regulatory pathways of meiotic differentiation in chicken PGCs.…”
Section: Specific Analysis Of the Target Gene Transcript For The Regumentioning
confidence: 99%
“…Evidence is mounting that RA may trigger entry into meiosis not just in mouse and rat, as detailed above, but also in chickens (Smith et al 2008) and amphibians (Wallacides et al 2009). Although a role for RA in initiating meiosis in humans has not been demonstrated so far, an anterior site of meiosis initiation -originating near the rete ovarii which connects the gonad and mesonephros -is observed in many mammalian species including humans (Byskov 1975, Bendsen et al 2006.…”
Section: How Does Ra Work Its Magic?mentioning
confidence: 99%